Հայաստանի եւ Թուրքիայի միջեւ առեւտրաշրջանառութեան վերլուծութիւն․ ռիսկեր/ հնարաւորութիւններ - Մնացականեան, Վիլէն (տպ. Atlas)
Armenian-Turkish relations have recently entered a new round of development. However, it is important to emphasize that any process in the new geopolitical realities is full of not only new opportunities but also risks. In this article, the author assesses the current state of foreign trade relations between Armenia and Turkey, as well as the economies and export structures of the two countries. Accordingly, the paper affirms that, compared with the Armenian economy, the Turkish economy is significantly more diversified and more flexible in the context of external economic shocks. A similar picture can be seen in foreign economic relations: Armenia's exports (both commodity groups and major partners) are significantly more concentrated, which creates additional risks in facing future external economic shocks. The study concludes that Armenia does not have mediation potential in the context of Turkey-EEU relations, because the main partners on this platform are Turkey and Russia. At the same time, the absence of a foreign economic policy developed by Armenia towards the Middle East makes it almost impossible to use Turkey as a mediator in these relations. The author's analysis of comparative advantages leads to the conclusion that Turkey has an advantage in bilateral relations in terms of product groups that are industrial products, while Armenia's advantages are mainly related to raw materials. In such a situation, the risks of external economic dependence on Turkey increase significantly. The paper concludes that in opening the borders between Armenia and Turkey, Armenia has to cultivate a strategic economic policy with Turkey to avoid dumpings and the loss of its tiny and weak local industries.
Keywords: Տնտեսութիւն